Strategi Komunikasi Efektif Pada Pemberdayaan Ekonomi Masyarakat Dalam Program Keluarga Harapan Di Kampung Kebet Kecamatan Bebesen Kabupaten Aceh Tengah - Sukri, Sukri; AB, Subhan; Fachri, Husni (Telangke:Jurnal Telangke Ilmu Komunikasi, 2024)
The aim of this research is to find out effective communication strategies in empowering the community's economy in PKH and what are the obstacles to PKH's effective communication strategies in empowering the community's economy in PKH in Kebet Village, Bebesen District, Central Aceh Regency. This research method uses qualitative methods with data collection techniques, namely observation, interviews and documentation. Determination of informants is based on a non-probability purposive sampling technique. The data analysis techniques used are data collection, data reduction, data presentation and verification. The results of the research show that the PKH program is carried out routinely every once in a while, providing education, direction, outreach and material about families of hope to its participants and has an impact. However, there are still many poor people who do not receive PKH. There are still many obstacles in the Family Hope Program (PKH), such as the low work ethic of the community targeted for empowerment, lack of monitoring or supervision and quality data in the empowerment process, inappropriate formulation of empowerment indicators or formulas, lack of coordination between the government and the community in the empowerment process, system bureaucratic administration.